Remodeling the tumor microenvironment: regulatory effects of β-sitosterol and luteolin on the immunosuppressive milieu in endometrial carcinoma and implications for combinatorial immunotherapy - Ji, Guojie; Wang, Pengbo; Kong, Zhihong; Cao, Xiangxiang; Shi, Xiaowei; Feng, Huigen; Hu, Huanhuan (Frontiers in Immunology, 2025)
Endometrial carcinoma (EC), particularly high-risk molecular subtypes like p53abn and NSMP, is frequently characterized by a tumor immunosuppressive tumor microenvironment (TME) that drives progression, metastasis, and resistance to therapy. This immunosuppressive milieu is orchestrated by key cellular components, including M2-polarized tumor-associated macrophages (TAMs), regulatory T cells (Tregs), myeloid-derived suppressor cells (MDSCs), PD-L1-expressing tumor cells, and pro-fibrotic cancer-associated fibroblasts (CAFs), which collectively inhibit effector T cell function and promote immune exclusion/desert phenotypes. Natural products offer promising multi-targeted strategies to remodel the TME. This review comprehensively summarizes the potent immunomodulatory effects of the phytosterol β-sitosterol (BSS) and the flavonoid luteolin (Lut) specifically within the EC TME. We detail how BSS and Lut synergistically reprogram TAMs towards an M1 phenotype, inhibit Treg differentiation/function and MDSC expansion, enhance CD8+ T cell recruitment, activation, and cytotoxicity (e.g., by downregulating PD-1/TIM-3), and suppress CAF-mediated immunosuppression and fibrosis. Mechanistically, these effects are achieved through targeting critical signaling pathways (STAT3, NF-κB, PI3K/AKT, Wnt/β-catenin) and modulating key chemokines/cytokines (e.g., reducing TGF-β, IL-10, CXCL12; increasing CXCL9/10, IFN-γ). Critically, BSS and Lut demonstrate significant potential to overcome resistance to immune checkpoint inhibitors (ICIs), particularly in immune-cold EC subtypes. By remodeling the immunosuppressive TME, BSS/Lut combinations can enhance ICI efficacy, as evidenced by preclinical data showing increased tumor suppression rates and T cell infiltration. While challenges remain, including EC-specific validation, bioavailability optimization, and molecular subtype stratification, BSS and Lut represent promising natural adjuvants for combinatorial immunotherapy, offering novel strategies to improve outcomes for patients with aggressive or treatment-refractory EC.